PENGARUH PEMANFAATAN ZEOLIT PELET TERAKTIVASI NaOH-FISIK DENGAN NORMALITAS TINGGI TERHADAP PRESTASI MESIN DIESEL 4-LANGKAH - Eko Hermawan; Herry Wardono; Harnowo Supriadi (FT UNILA, 2026)
Zeolites are alumina silicate compounds which have the ability as adsorbents. In this study, the ability of zeolite was used to filter air for the combustion process in order to improve the performance of a 4-strokes diesel engine. The zeolite activated by NaOH was used to clean the surface of the pores and get rid of impurities, so that the zeolite could bind nitrogen gas dan water vapor when used. In these tests, zeolites were activated by NaOH using 1N;2N;3N;4N normality and physical activation at 200OC for 1 hour. The zeolites were then formed into tablets and packaged in a frame that was placed on diesel engine air filter. The experiments were operated at engine speeds of 1500, 2000, 2500, 3000 rpm. It is found that chemically and physically activated zeolites could improve the performance of the engine. The results showed that the best increase of averagebrake power was 1.6605% occurring at zeolite activated using NaOH 1N and the best decrease of avarage brake specific fuel consumption was 2.836% using also NaOH 1N – physical activated zeolite. Both occurred at dense zeolites arrangement.